2019
DOI: 10.3390/a12090194
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady State Lightweight Iris Certification Based on Multi-Algorithm Parallel Integration

Abstract: Aimed at the one-to-one certification problem of unsteady state iris at different shooting times, a multi-algorithm parallel integration general model structure is proposed in this paper. The iris in the lightweight constrained state affected by defocusing, deflection, and illumination is taken as the research object, the existing algorithms are combined into the model structure effectively, and a one-to-one certification algorithm for lightweight constrained state unsteady iris was designed based on multi-alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In other words, the pore textures artificially render the discontinuity of the constitution of a liquid film at the interface, causing the unstable interfacial contact (i.e., solid–solid contact with a heterogeneous interface caused by the pore textures) for the boundary lubrication regime, giving rise to high COF values. Previously, several works , also showed that microtexturing could delay the transition of the lubrication regimes (e.g., with the extension of the boundary lubrication regime) due to the discontinuity of the liquid at the heterogeneous interface caused by the textures, leading to an increase in the COF value under the boundary and mixed lubrication regimes. The present results suggest such effects are still valid even with nanotexturing.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the pore textures artificially render the discontinuity of the constitution of a liquid film at the interface, causing the unstable interfacial contact (i.e., solid–solid contact with a heterogeneous interface caused by the pore textures) for the boundary lubrication regime, giving rise to high COF values. Previously, several works , also showed that microtexturing could delay the transition of the lubrication regimes (e.g., with the extension of the boundary lubrication regime) due to the discontinuity of the liquid at the heterogeneous interface caused by the textures, leading to an increase in the COF value under the boundary and mixed lubrication regimes. The present results suggest such effects are still valid even with nanotexturing.…”
Section: Resultsmentioning
confidence: 99%
“…Multialgorithm parallel integration: An unsteady state multialgorithm parallel integration decision recognition algorithm in [18]; 6.…”
Section: Dpso-certification Functionmentioning
confidence: 99%
“…The existing framework is improved and tested through the public iris set, which proves that the framework is feasible, such as iris specific Mask R-CNN [12] and deep learning frameworks such as capsule neural networks under lightweight data structures [13], as well as existing deep learning frameworks specifically for iris recognition, such as DeepIris [14] and DeepIrisNet [15]. In research on the multi-state iris, the unsteady-state features are transformed into steady-state features through image processing and other methods [16], and the iris features are expressed through multiple recognition methods and weighted fusion [17] or the final result is obtained based on a credibility decision [18].…”
mentioning
confidence: 99%
“…As a result, additional studies have begun to focus attention on the overall relationship and design for the framework, such as iris-specific Mask R-CNN [9], to modify the exist-ing framework, integrate the positioning into the iris recognition process, and publicly test the iris set to prove the feasibility of the framework. In research on the unsteadystate iris, the unsteady-state features are transformed into steady-state features through image processing and other methods [10], and the iris features are expressed through multiple recognition methods and weighted fusion [11] or the final result is obtained based on a credibility decision [12]. For setting of iris concept labels, research on biomimetic cognition [13] is an important direction, i.e., determination of how to first summarize a feasible recognition model in the case of a small number of initial training samples, and with increases in the number of recognitions and available training samples, how to further effectively judge whether the current structure cannot meet the existing situation and requires users to retrain [14].…”
Section: Introductionmentioning
confidence: 99%